Design enhancement of sustainable glass fiber reinforced polymer (GFRP) cross arm - Alhayek A.; Syamsir B.A.; Anggraini V.; Muda Z.C.; Nor N.M. (Alpha Publishers, 2023)
Fibre Reinforced Polymer (FRP) mixtures are widely used in construction fields, such as repair, restoration, reinforcement and new construction, properties like high corrosion resistance, electrical insulation characteristics low thermal conductivity, high strength, and, high strength-weight ratio. Therefore, like their metal equivalents, these composites are not isotropic, that provides more difficult design and development methods for interact about an economical design that could maintain every types of loads. Therefore, this paper aimed to study and enhance a design of a transmission tower cross arm made of Glass Fiber Reinforced Polymer (GFRP) carrying a 275 kV cable by developing a numerical model of a GFRP cross arm. The results showed that stresses developed in the composites were within the safe range. In addition, the cross arm was shown to be governed by the serviceability requirement and it was safe against multiple failure criteria such as fibers and delamination failure. Furthermore, the results showed that the total deformation was reduced by 14.2% by adding 1-meter GFRP sleeves to all members near the cable and by 20.7% if Carbon Fiber Reinforced Polymer (CFRP) sleeves were used. 2020 Alpha Publishers.